2016
DOI: 10.21608/eajbsa.2016.12853
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of Entomopathogenic Nematodes Steinernema glaseri and Heterorhabditis bacteriophora Poinar (HP88 strain) Against the Black Cutworm, Agrotis ipsilon.

Abstract: www.eajbs.eg.net Virulence of Entomopathogenic Nematodes Steinernema glaseri and Heterorhabditis bacteriophora Poinar (HP 88 strain) Against the Black Cutworm, Agrotis ipsilon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
5
7
0
Order By: Relevance
“…In addition, Sayed (2011) found a significant decrease in total body tissue homogenate of G. mellonella treated with normal and 2 Gy irradiated S. carpocapsae. Same results obtained by Hassan, Shairra, and Ibrahim (2016) on Agrotis ipsilon treated with S. glaseri and H. bacteriophora. The reason for total protein reduction may attributed to the breakdown of total proteins by proteases; the important extracellular enzymes secreted from the nematode symbiotic bacteria once entering the host body (Bowen, Blackburn, Rocheleau, Grutzmacher, Ffrench, e, & Constant, 2000, 2003Marokhazi et al, 2007).…”
Section: Discussionsupporting
confidence: 77%
“…In addition, Sayed (2011) found a significant decrease in total body tissue homogenate of G. mellonella treated with normal and 2 Gy irradiated S. carpocapsae. Same results obtained by Hassan, Shairra, and Ibrahim (2016) on Agrotis ipsilon treated with S. glaseri and H. bacteriophora. The reason for total protein reduction may attributed to the breakdown of total proteins by proteases; the important extracellular enzymes secreted from the nematode symbiotic bacteria once entering the host body (Bowen, Blackburn, Rocheleau, Grutzmacher, Ffrench, e, & Constant, 2000, 2003Marokhazi et al, 2007).…”
Section: Discussionsupporting
confidence: 77%
“…The obtained data show that the damage in DNA parameters were increased proportionally with irradiation doses. These data agreed with those obtained by Galea et al (2016); Hassan et al (2016) and Enciso et al (2018) who studied the effect of gamma irradiation on Heterorhabditis and Steinernema species. They found that, the efficiency was enhanced against G. mellonella.…”
Section: Discussionsupporting
confidence: 91%
“…This efficiency may be attributed to the damage of the antioxidant contents in the insect larval body which could cause the faster larval death (Sayed et al, 2015). The total protein was decreased in the irradiated IJs of S. scapterisci and H. bacteriophora and in turn, decreased in the homogenecity of the G. mellonella body tissue (Sayed, 2011) and of Agrotis ipsilon body tissue (Hassan et al, 2016). These reductions of protein may be due to the breakdown proteases effect on the total protein and the effect of the extracellular enzymes which secreted by the nematode symbiotic bacteria i.e Xenorhabdus for steinernematids and Photorhabdus for herterorhabditids (Poinar, 1979) in the insect body.…”
Section: Discussionmentioning
confidence: 99%
“…were with the highest activity, giving a 100% mortality to S. littoralis larvae in a Petri dish assay after 24 h post exposure, while S. monticolum caused the highest mortality rate for larvae (100%) at the concentration of 1600 IJs/dish for all larval instars. Despite the results obtained from Hassan et al (2016) who reported that the effect of S. glaseri was greater than the nematode, H. bacteriophora, the obtained results agree with those of Shairra and Nouh (2014) who reported that higher concentrations of nematodes caused an acute effect, while the latent effect was observed in the case of lower ones and Shairra (2007) who found a positive relationship between concentration and larval mortality, mainly due to the concentration of IJs. However, the defense reactions against the nematodes and their associated bacteria may play an important role.…”
Section: The Bioassay Of Heterorhabditis Bacteriophora (Hp88)supporting
confidence: 73%